The Forum for East Asia-Latin America Cooperation (FEALAC) as bi-regional south-south cooperation experience - Funes, Leonardo Manuel (2014)
The Forum for East Asia-Latin America Cooperation is clearly an experience of bi-regional South-South cooperation that opts for a cooperative relationship under conditions of reciprocity, understanding countries as partners and developing their projects based on consensus regardless of relative development.